The Virtual Fashion in the Global Apparel Industry in the Post-Epidemic Era (Journal of Fiber Bioengineering and Informatics, 2022)
The global economy has experienced a downturn due to the COVID-19 epidemic, and the entire apparel industry has been hit hard. However, in the post-epidemic era, the digital trend of the world has become more pronounced. The virtual consumer market and virtual fashion took this opportunity to overgrow. More and more people are willing to spend money on virtual products. In a way, virtual fashion is the acceleration and continuation of future fashion trends. The most crucial difference between virtual and physical fashion is that the latter does not undergo physical production. Instead, virtual clothing can be purchased and “worn” immediately. More and more fashion brands have paused traditional fashion shows in favor of visuals such as video game collaborations, mobile apps, virtual icons, virtual showrooms, and virtual clothing brands. This paper compares and analyzes ten international brands associated with virtual fashion through data collection and case studies. It shows that with the help of modern cutting-edge technology, the traditional apparel industry has ushered in a new transformation point. New virtual fashion will gradually enter our daily life from the experimental field, driving the transformation of the apparel industry.
Keywords: Virtual Fashion; Virtual Clothing; Digital Clothing; Virtual Economy; Fashion Industry